Molecular Determinants of Dissolved Organic Matter Reactivity in Lake Water - Mostovaya, Alina; Hawkes, Jeffrey A.; Dittmar, Thorsten; Tranvik, Lars J. (Frontiers in Earth Science, 2017)
Lakes in the boreal region have been recognized as the biogeochemical hotspots, yet many questions regarding the regulators of organic matter processing in these systems remain open. Molecular composition can be an important determinant of dissolved organic matter (DOM) fate in freshwater systems, but many aspects of this relationship remain unclear due to the complexity of DOM and its interactions in the natural environment. Here, we combine ultrahigh resolution mass spectrometry (FT-ICR-MS) with kinetic modeling of decay of >1300 individual DOM molecular formulae identified by mass spectrometry, to evaluate the role of specific molecular characteristics in decomposition of lake water DOM. Our data is derived from a four months microbial decomposition experiment, carried out on water from three Swedish lakes, with the set-up including natural lake water, as well as the lake water pretreated with UV light. The relative decay rate of every molecular formula was estimated by fitting a single exponential model to the change in FT-ICR-MS signal intensities over decomposition time. We found a continuous range of exponential decay coefficients (kexp) within different groups of compounds and show that for highly unsaturated and phenolic compounds the distribution of kexp was shifted towards the lowest values. Contrary to this general trend, plant-derived polyphenols and polycondensed aromatics were on average more reactive than compounds with an intermediate aromaticity. The decay rate of aromatic compounds increased with increasing nominal oxidation state of carbon, and molecular mass in some cases showed an inverse relationship with kexp in the UV-manipulated treatment. Further, we observe an increase in formulae-specific kexp as a result of the UV pretreatment. General trends in reactivity identified among major compound groups emphasize the importance of the intrinsic controllers of lake water DOM decay. However, we additionally indicate that each compound group contained a wide spectrum of reactivities, suggesting that high resolution is needed to further ascertain the complex reasons behind DOM reactivity in lake water.